The effect of using sustainable balanced scorecard in the relationship between strategic cost management methods and strategic performance of Jordanian Public Shareholding Industrial Companies (Entrepreneurship Journal for Finance and Business, 2025)
This study aimed to explore the effect of using a sustainable balanced scorecard in the relationship between strategic cost management methods and strategic performance of Jordanian public shareholding industrial companies by shedding light on the most important modern administrative and accounting techniques used by advanced industrial companies in managing their costs and following up on the implementation of necessary corrective and preventive measures to enhance areas of strength and address areas of weakness in their strategic performance. The study population consisted of all employees in Jordanian public shareholding industrial companies. To achieve the objectives of the study, a questionnaire was developed and distributed to (205) individuals working in Jordanian public shareholding industrial companies. (158) questionnaires were retrieved, of which (146) were valid for analysis. To test the hypotheses, Structural Equation Model (PLS- SEM).The study found that there is an effect of using a sustainable balanced scorecard in the relationship between total quality management method and strategic performance of Jordanian public shareholding industrial companies. However, the results of the study indicated no effect of using a sustainable balanced scorecard in the relationship between other strategic cost management methods (Target costing method, comparative measurement method) and the strategic performance of Jordanian public shareholding industrial companies. Based on the results of this study, the researchers reached several recommendations, The most important was: the necessity of Jordanian public shareholding industrial companies to enhance the implementation of strategic cost management methods, especially the target costing method, due to its positive effect on the use of a sustainable balanced scorecard. Moreover, it is essential to reconsider the application of comparative measurement method and work on its enhancement to be more effective in supporting the use of a sustainable balanced scorecard and improving strategic performance